ROLE AND IMPORTANCE OF ANTİOXİDANTS İN SCİENTİFİC RESEARCH - Mukhammadıy Khakimov (Western European Studies, 2025)
Antioxidants are compounds that are increasingly important in modern medicine and health sciences. These molecules play a critical role in protecting cells and tissues by preventing oxidative stress caused by free radicals. Oxidative stress occurs when free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), interact with cellular components, damaging DNA, proteins, and lipids. This process is closely associated with many pathological conditions such as cancer, cardiovascular diseases, neurodegenerative disorders (Alzheimer's, Parkinson's, etc.), and even aging. Antioxidants help prevent cellular damage by neutralizing these harmful molecules.
Keywords: harmful; neurodegenerative; associated; aging